Some results of NAA collaborative study in white rice performed at Dalat Nuclear Research Institute - T., Q. Thien; C., D. Vu; H., V. Doanh; N., T. Sy (Nuclear Science and Technology, 2014)
White rice is a main food for Asian people. In the framework of Forum for Nuclear Cooperation in Asia (FNCA), therefore, the eight Asian countries: China, Indonesia, Japan, Korea, Malaysia, the Philippines, Thailand and Vietnam selected white rice as a common target sample for a collaboration study since 2008. Accordingly, rice samples were purchased and prepared by following a protocol that had been proposed for this study. The groups of elements that were analyzed by using neutron activation analysis in the white rice samples were toxic elements and nutrient elements, including: Al, As, Br, Ca, Cl, Co, Cr, Cs, Fe, K, Mg, Mn, Na, Rb and Zn. The analytical results were compared between the different countries and evaluated by using the Tolerable Intake Level of World Health Organization (WHO) and Recommended Dietary Allowance or Adequate Intake (AI) of the U.S. Institute of Medicine (IOM) guideline values. These data will be very useful in the monitoring of the levels of food contamination and in the evaluation of the nutritional status for people living in Vietnam and other Asian countries.